2020
DOI: 10.1186/s43042-019-0043-0
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α -308 G>A and IL10 -1082A>G polymorphisms as potential risk factors for lymphoproliferative disorders in autoimmune rheumatic diseases

Abstract: Background: Chronic inflammation with sustained unregulated immune stimulation in autoimmune rheumatic diseases (ARD) may be a risk factor for developing lymphoproliferative disorders (LPD). Markers of ARD activity as high erythrocyte sedimentation rate or erosive joint diseases and the development of B-symptoms were accounted as risk factors for LPD development. We investigated the association of five inflammatory cytokine genes single nucleotide polymorphisms (SNPs): TNF-α-308G>A; TGF-β1 gene codon 10 T>C an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In patients with NHL, high levels of TNF–α were been found to be associated with negative prognosis, high frequency of relapse and reduced survival [ 10 ]. Similarly, it was reported that the G>A genotype and A allele of rs1800629 SNP increase susceptibility to NHL and autoimmune rheumatic disease with lymphoproliferative disorders [ 14 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with NHL, high levels of TNF–α were been found to be associated with negative prognosis, high frequency of relapse and reduced survival [ 10 ]. Similarly, it was reported that the G>A genotype and A allele of rs1800629 SNP increase susceptibility to NHL and autoimmune rheumatic disease with lymphoproliferative disorders [ 14 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that the A allele of the altered TNF–α promotor region due to rs1800629 SNP leads to higher transcriptional activity than its ancestral G allele, causing increased production of TNF–α by B and T cells [ 23 , 24 , 25 , 26 ]. High levels of TNF–α have been found in patients with childhood ALL in comparison to normal control subjects [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies have also found that the allele A of the TNF-α-308 gene (TNF-α-308A) is associated with the risk of coronary heart disease [16,17]. The multifunctional proinflammatory cytokine TNF-α influences several risk factors for cardiovascular diseases, in particular, insulin resistance, dyslipidemia, endothelial dysfunction and endothelial activation of cell adhesion molecules [18].…”
Section: Polymorphism Of Tumor Necrosismentioning
confidence: 99%